2017
DOI: 10.18535/ijmsci/v4i4.03
|View full text |Cite
|
Sign up to set email alerts
|

Profile of utero-cervical lesions in peri- & post-menopausal women in Kumaon Region of Uttarakhand: An Institutional study

Abstract: INTRODUCTION PAP smear is an important tool which compliment histopathology in detection of various cervical lesions. Since last few decades, it is becoming easy and cost-effective way for early detection of pre-cancerous and cancerous cervical lesions. AIMS/OBJECTIVES: The objective of this study is to evaluate the utero-cervical lesions in peri-& post-menopausal age group by Pap smear method; to study the distribution of cervical lesions and to correlate cytology with histopathology wherever available. MATER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…Various researchers had done studies to evaluate the efficiency of pap smear cytology for the diagnosis of non-neoplastic and neoplastic cervical lesions. 14,15 In the current study, sensitivity of the pap smear was found to be 90.16%, which indicates pap smear was correctly able to diagnose 90.16% cases of neoplastic cervical lesions, while the specificity was found to be 85.22%, which indicates its ability to correctly diagnose 85.22% cases of non-neoplastic cervical lesions. Our study also revealed PPV and NPV of the pap smear was 89.43% and 86.2%, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 47%
“…Various researchers had done studies to evaluate the efficiency of pap smear cytology for the diagnosis of non-neoplastic and neoplastic cervical lesions. 14,15 In the current study, sensitivity of the pap smear was found to be 90.16%, which indicates pap smear was correctly able to diagnose 90.16% cases of neoplastic cervical lesions, while the specificity was found to be 85.22%, which indicates its ability to correctly diagnose 85.22% cases of non-neoplastic cervical lesions. Our study also revealed PPV and NPV of the pap smear was 89.43% and 86.2%, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 47%
“…9,10 Previously, various studies had been done to assess the diagnostic efficacy of pap smears for the diagnosis of various cervical lesions. [22][23][24] In our study, sensitivity and specificity of pap smears for the diagnosis of neoplastic cervical lesions was 70.54% and 81.9% respectively, while PPV and NPV were 82.72% and 69.35% respectively (Table 4). These findings are in agreement with those reported by previous researchers 4,13,16,18 (Tables 4 and 6).…”
Section: Discussionmentioning
confidence: 57%